2021
DOI: 10.3399/bjgpo.2021.0085
|View full text |Cite
|
Sign up to set email alerts
|

Engagement with community liver disease management across the UK: a cross-sectional survey

Abstract: BackgroundLiver disease is an increasing cause of premature mortality in the UK. Its management in primary care is not well understood. It is unclear what role commissioning bodies are playing in liver disease in the UK.AimThe aim of this study was to assess the level of engagement with community chronic liver disease management amongst CCGs and health authorities across the UK.Design & settingA cross-sectional survey to all UK CCGs and health authorities.MethodSurvey questions were developed by the Britis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Attempts to rectify these inequalities in access has been facilitated through the National Pathology Exchange hosted by the NHS, allowing any lab across the UK to request and access an ELF test 32. Similar accessibility issues were found with TE, with only 19% of CCGs in England having access compared with all health boards in Wales (100%) 26. NICE is set to publish guidance supporting the use of TE in the primary and community care setting in 2023 which should also begin to ameliorate issues around accessibility 33.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Attempts to rectify these inequalities in access has been facilitated through the National Pathology Exchange hosted by the NHS, allowing any lab across the UK to request and access an ELF test 32. Similar accessibility issues were found with TE, with only 19% of CCGs in England having access compared with all health boards in Wales (100%) 26. NICE is set to publish guidance supporting the use of TE in the primary and community care setting in 2023 which should also begin to ameliorate issues around accessibility 33.…”
Section: Discussionmentioning
confidence: 73%
“…When examining pathways in primary or secondary care that use NITs of liver fibrosis to guide management of patients with, or at risk of liver disease, we found 65.2% of respondents, representing 40.1% of acute hospital trusts, stating they did have a pathway in place in 2021. This contradicts a recent comprehensive cross-sectional study by Jarvis et al of 99% CCGs and health boards in the UK in 2020 26. The authors found 40% had a primary care pathway to evaluate abnormal liver blood tests and 29% had a pathway to manage common liver diseases 26.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A national survey by Jarvis et al of clinical commissioning groups across the UK, with 99% of groups responding, found only 29% and 40% of regions had some pathway in place to manage liver disease or abnormal LFTs respectively in the primary care setting (41). This is despite all the pathways presented in this review having demonstrated superiority over "standard of care" in detection of liver disease, with robust cost benefit being illustrated in modelling from iLFTs and Scarred Liver Project.…”
Section: Entry Point To Testingmentioning
confidence: 78%
“…Several research studies have shown pathways to find chronic liver disease in the community lead to an increase in detection of significant disease 5 , 6 and are cost-effective. 7 Despite this, implementation of these pathways has been slow and partial 8 and there has been little prospective study of how they may fit within routine primary care work.…”
Section: Introductionmentioning
confidence: 99%